The language essence of rational cognition with some philosophical consequences - Čulina, Boris (2021)
The essential role of language in rational cognition is analysed. The approach is functional: only the results of the connection between language, reality and thinking are considered. Scientific language is analysed as an extension and improvement of everyday language. The analysis gives a uniform view of language and rational cognition. The consequences for the nature of ontology, truth, logic, thinking, scientific theories, and mathematics are derived.